(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, the “STORY”, which is an e-commerce mobile platform, is developed based-on machine learning techniques in order to consolidate selling methods into a unified, efficient, and personalized environment. Also, to elevate user experiences, and cultivate a thriving e-commerce environment in Libya. STORY is designed to serve the needs of both customers and merchants, aiming to bridge the gap between consumer demands and efficient business interactions. This platform strives to provide customers with a wide range of services and functions that match their preferences, while empowering merchants with a user-friendly mobile interface for effective business management. Among its notable features, STORY boasts an image-based search function, which simplifies the process of searching for desired or similar products. Additionally, the platform integrates an intelligent recommendation system capable of tracking and analyzing customer behaviors within the platform. This system collects pertinent data to offer personalized product recommendations and tailored offers, elevating the shopping experience. The system underwent an evaluation via a questionnaire, which had overwhelmingly positive results. User feedback and satisfaction regarding the system’s functionalities and performance were notably favorable.